الثقافة التنظيمية كدعامة للمسؤولية الاجتماعية في منظمات الأعمال الجزائرية: دراسة حالة اتصالات الجزائر للهاتف النقال موبيليس - فلاق، محمد; يوسف، أحمد (المركز الجامعي علي كافي بتندوف, 2016)
This study aims to determine the impact of organizational culture in supporting and activating the social responsibility of the company Algerie Telecom's Mobilis, a mobile phone and that is one of the leading organizations in the telecommunications market in Algeria. It also aims to gauge the strength of the relationship between organizational culture and corporate social responsibility. To achieve the objectives of the study were distributed), 105 (a questionnaire on a sample of workers Mobilis company. In order to achieve the goal of the study above and answer the questions of the problem and test the validity of hypotheses, the researcher adopted the resolution as a key tool to gather information and data and dealt with this data using a group of statistical techniques appropriate to the nature of the research, such as the arithmetic mean and coefficient of correlation and carried out using the Statistical (SPSS) on the computer. And the results showed that there is a strong influence of the variable of organizational culture in the activation of social responsibility, in addition to a statistically significant effect of the values and customs and traditions in the activation of social responsibility.
Keywords: الثقافة التنظيمية -- المسؤولية الاجتماعية -- منظمات الأعمال -- الجزائر -- شركات الاتصالات